Penguuatan Perilaku Salbia Sebagai Alternatif Perilaku Rasional Birokrasi pada Pemilihan Umum - Hamim, Udin; Mahmud, Ramli (Universitas Negeri Malang, 2022)
The purpose of this study is to analyze the portrait of bureaucratic political behavior in general elections and to strengthen salbiyah behavior as an alternative to the rational attitude of the bureaucracy. This study uses qualitative methods with a phenomenological approach. The results of the study show that the portrait of bureaucratic political behavior in general elections is mapped in two approaches, namely the sociological and psychological approaches. Bureaucratic political behavior with a sociological approach determines political choices based on the candidate’s job and affiliation with social organizations that are influenced by culture. Bureaucratic political behavior with a psychological approach determines political choices based on one’s interest in political parties and orientation towards prospective candidates who are influenced by political issues. Strengthening salbiyah behavior as an alternative to bureaucratic rational attitudes is carried out by implementing obedience and obedience to leaders, firmness of principles, consistency with applicable regulations, and the wisdom of a leader (ta’uwa).